Paper of Tax Courting and Income Tax Rates Based on Chapter 21 for Freelances Workers and Non-permanent Employees - Efrata Purbanta Aginta Purba; Riki Oktaries T; Afif Alfac; Galuh Tresna Murti (Jurnal Riset Perpajakan: Amnesty, 2023)
This research aims to write a paper on Article 21 income tax deductions and rates on honoraria for casual workers and non-permanent employees. The research method used is to collect data from various sources such as literature, financial reports and tax reports. This research also shows that Article 21 income tax deductions and rates for the honorarium of freelance workers and non-permanent employees are different, determined by the category of worker, amount of income and applicable tax rates, and you can find out (1) the regulations that apply to Article 2 Income Tax Withholdings and Rates. 21 on Honorarium for freelance workers and non-permanent employees; (2) the type of tax that applies to the Honorarium of freelance workers and non-permanent employees; (3) withholding standards and tax rates applicable to the Honorarium of freelance workers and non-permanent employees; and (4) how to calculate withholding and tax rates that apply to the Honorarium of freelance workers and non-permanent employees. The results of this research aim to provide a deeper understanding of Article 21 Income Tax Withholdings and Rates on Honorarium for casual workers and non-permanent employees, thereby enabling companies to organize tax management efficiently